Transnational Turkish Islam - Sunier, Thijl. author. aut Link
VIII, 138 p.
Keywords: Transnational Turkish Islam provides an overview of Turkish organized Islam in seven European countries. It shows how Turkish Islamic organizations have developed from typical migrant associations in the 1970s and 1980s into present-day European Islamic associations with their own cultural and religious specificities and agendas.